Evaluating Financial Performance of Investment Companies Using the Treynor-Black Method: An Analysis of Risk-Adjusted Returns and Portfolio Optimization - Abdul Manap; Glorya Glorya; Rievay Rievay; Septina Gabriela; Yumia Ancella Zahra (Journal on Economics, Management and Business Technology, 2024)
This research evaluates the financial performance of investment companies using the Treynor-Black Method, which optimizes portfolios by combining high-alpha assets with a market portfolio to enhance risk-adjusted returns. The study applies this method to a sample of investment companies to examine its effectiveness in improving key performance metrics, including the Sharpe Ratio, Treynor Ratio, and Jensen’s Alpha. Findings indicate that the Treynor-Black Method substantially improves portfolio performance, with optimized portfolios showing higher Sharpe and Treynor Ratios and positive Jensen’s Alpha. These results suggest effective management of systematic risk and added value through active management. Nonetheless, the research acknowledges limitations such as dependence on historical data, potential data quality issues, and challenges in alpha and beta estimation. These constraints highlight the need for cautious interpretation and suggest future research directions, including the use of real-time data and alternative optimization approaches. The study provides practical insights for investment managers, offering a refined framework for portfolio construction and performance evaluation. It contributes to the field by validating and extending the Treynor-Black Method, enhancing strategies for aligning portfolios with risk-return objectives.